India Enchants: the Burst of Blossoms; Jhabvala’S First Phase Novels: The Transformation of Indian Society in the Post-Independence Era (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The impact of modern Western ideology was seen at manylevels of Indian life after Independence. An era of science, technology and modern economy was being usheredin.  Education in general and that of womenin particular was gaining momentum.